The multilateral aid system: An assessment following the major replenishments of 2013 - Richard Manning (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The paper assesses the multilateral development financing system in the light of the replenishments of three key funds in 2013. It argues that the replenishments showed strong continuing support for each institution, but identifies challenges emerging from the reliance on traditional donors and the limited success in engaging major emerging economies. It underlines the significance of recent and prospective falls in the recipient client base, and notes the shifting balance between performance and need/fragility in determining multilateral aid allocations. The paper argues that both general and special purpose funds have their place, but that to sustain ownership in the more aid-dependent countries a 'think twice' policy remains appropriate before establishment of new special purpose funds.
Keywords: 330; multilateral aid system; International Development Association; African Development Fund; Global Fund; OECD/DAC; development finance